Spatio-temporal Assessment of the Bagmati River Water Using Real-Time Data - Adhikari, Nanda Bikram; Rawal, Narendra Bahadur; Joshi, Jarina; Pradhananga Adhikari, Mandira (Journal of Nepal Biotechnology Association, 2026)
Water pollution and tributaries are deteriorating the water quality of the Bagmati river, especially in Kathmandu valley. Mostly, the water quality of the Bagmati river is characterized using traditional methods, therefore, have been unable to identify sources of pollutants. In this study, real-time continuous monitoring and collecting data in a large volume using sophisticated sensors were performed. The diurnal, spatial, daily and temporal variations of physicochemical water quality parameters were presented for an in-depth understanding of the real status of the Bagmati river. The spatial variation of water quality parameters indicated that conductivity was drastically increased (605.41 ± 8.9 to 1145.30 ± 9.32 µS/cm), and the oxidation-reduction potential (ORP) was excessively reduced (28.09 ± 6.88 to -306.75 ± 4.95 mV) after mixing of the tributaries. The high conductivity (>605.41 ± 8.9 µS/cm and negative ORP values (-40.29 ± 32.14 to -306.75 ± 4.95 mV) are an indication of a sewer connection. Daily, diurnal and temporal variations suggested that the Bagmati river is always polluted with a negative ORP value (<-50 mV) in the daytime, and river quality worsens day to day. In conclusion, it is important to control the mixing of effluent into the Bagmati river and its tributaries to revive the river ecosystem and prevent loss of survives.